2005
DOI: 10.1016/j.tranpol.2005.03.003
|View full text |Cite
|
Sign up to set email alerts
|

How do individuals adapt their personal travel? Objective and subjective influences on the consideration of travel-related strategies for San Francisco Bay Area commuters

Abstract: This study operationalizes the conceptual analysis presented in a companion paper, to examine the effects of objective and subjective variables on the consideration of 16 travel-related strategies reflecting a range of individuals' potential reactions to congestion. Using 1283 commuting respondents to a 1998 survey conducted in the San Francisco Bay Area, binary logit models were developed for the consideration of each individual strategy. The proportion of information explained by these models ranges from 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 16 publications
2
43
0
Order By: Relevance
“…Hence, the effort involved is higher for high frequency drivers. This is in line with Gärling et al, (2004) and Cao and Mokhtarian (2005), who found that travelers prefer low effort responses over high effort responses. A second explanation is that the added value of additional rewards depends on the amount already gained, in the sense that the marginal utility of reward decreases.…”
Section: Habitual Behavior and Experiencesupporting
confidence: 90%
“…Hence, the effort involved is higher for high frequency drivers. This is in line with Gärling et al, (2004) and Cao and Mokhtarian (2005), who found that travelers prefer low effort responses over high effort responses. A second explanation is that the added value of additional rewards depends on the amount already gained, in the sense that the marginal utility of reward decreases.…”
Section: Habitual Behavior and Experiencesupporting
confidence: 90%
“…Hilderbrand [59] used socio-demographic variables to cluster elderly people in six lifestyle groups and used these clusters to run a micro-simulation of an activity based model. A series of studies tried to investigate the role of personality traits: Mokhtarian, Salomon and Redmond [60] defined four typologies (adventure seekers, organizers, loners and calm people) thanks to a 17-item questionnaire and Cao and Mokhtarian [61,62] used an 18-item questionnaire that again individuated four lifestyles. Findings showed that adventure-seekers travel the most and are more flexible and that they tend to consider a wider set of strategies to reach their personal travel interests [63].…”
Section: Strengths and Weaknesses Of Application To Transport Sector mentioning
confidence: 99%
“…In the case of road pricing acceptability, the use of hybrid discrete choice models with the incorporation of psychological factors leads to a more behaviorally realistic representation of the choice process, and consequently has a better explanatory power (Cao and Mokhtarian, 2005;Heath and Gifford, 2006;Duarte et al, 2009;Karash et al, 2008). Thus a sequential maximum likelihood estimation method is used to integrate latent variables in discrete choice models.…”
Section: Modeling Acceptability With Latent Variablesmentioning
confidence: 99%